Financial costs to the U.S. Army for suicides by newly enlisted Soldiers. Issue 5 (18th June 2021) - Schaughency, Katherine C. L.; Watkins, Eren Youmans; Barnes, Stephen; Smith, Jacob D.; Forrest, Lanna J.; Christopher, Phyon K.; Anke, Kirsten M.; Sikka, Rachana; Pecko, Joseph A.; Cox, Kenneth L.
Abstract: Objective: To estimate the financial burden to the U.S. Army of suicide by enlisted Soldiers during their first year of service. Methods: This analysis included new Army enlisted Soldiers who started initial entry training from October 2012 through September 2016 and subsequently died by suicide within their first year of service. Outpatient and inpatient direct medical, direct nonmedical, recruiting, and training costs to the Army were calculated. Results: During the 48‐month observational study period, 29 Soldiers died by suicide within their respective first year of service. The described financial costs accrued by the Army as a result of these deaths were $152, 271—with an average of $6, 091 per healthcare utilizer. Recruiting and training costs were $1, 115, 860 for all suicide cases. Conclusion: Average direct cost per healthcare utilizer increased during a Soldier's first year of service. This may be associated with the transition through different phases of training and to the first operational duty station. Public Health Implications: Results obtained through this cost‐of‐illness analysis may serve as baseline metrics to inform future cost‐effectiveness studies.